Investigation the effect of melt and wet granulation on the dissolution characteristics of sodium diclofenac as a model drug - الحاج, ياسمين; تميم حماد; وهاد إبراهيم (Latakia University Journal -Medical Sciences Series, 2024)
This study aims to prepare granules using both wet granulation and melt granulation techniques, then compare the effect of different granulation techniques on the release rate of diclofenac sodium, the active ingredient model, to determine whether it is possible to use melt granulation as an alternative technology to get rid of the problems of wet granulation. Several formulations of diclofenac sodium granules were prepared using stearic acid as an excipient to modify the release in different ratios (3:1, 5:1, drug: stearic acid) using wet granulation and melt granulation. The various properties of the granules were evaluated, including flowability, content determination, size distribution, and moisture, and then the effect of granulation technique and the amount of stearic acid on the release rate of diclofenac sodium was studied. The results showed that melt granulation delayed the release with a statistically significant difference compared to wet granulation. It was also shown that when the amount of stearic acid was increased, the released amount of diclofenac sodium decreased in both techniques.